Early corticosteroid withdrawal regimen in a living donor kidney transplantation program - Bansal, S. B. (Medknow Publications & Media Pvt Ltd, 2014)
Steroids have been the essential component of transplant immunosuppression. Recently, with availability of better immunosuppressive agents, many centers have started steroid free transplant with good success rates. We analyzed the outcomes of early corticosteroid withdrawal (CSW) protocol in our living donor kidney transplant programme. We included 73 patients on CSW protocol on basiliximab + tacrolimus and mycophenolate mofetil and compared them with 67 recipients on similar regimen with corticosteroids (CSs). CSW group received prednisolone 40 mg on day 1, which was stopped on day 5. Outcomes were evaluated in terms of acute rejection (AR), infections, new onset diabetes after transplant (NODAT), renal function and graft or patient loss. In CSW group, 15/73 (20.5%) patients developed AR, when compared to 5/67 (7.5%) in CS group, (P = 0.02). Biopsy proven acute rejection was seen in 12/72 (16.6%) in CSW group and 5/67 (7.5%) in CS (P = 0.1). One patient in CSW group developed antibody mediated rejection. NODAT was similar (9% in CS vs. 3.7% in CSW, P = 0.09), but infections were higher in CSW group (20.5% vs. 7.5%, P = 0.02). Mean serum creatinine was similar at 6 months (1.24 ± 0.6 in CS and 1.25 ± 0.3 in CSW, P = 0.9). Graft survival was 100% and 97% (P = 0.1) and patient survival was 98.6% and 98.5% (P = 0.9) in CSW and CS groups. Early corticosteroid withdrawal with basiliximab induction was associated with increased risk of AR but did not have any effect on short term graft and pateint survival.